TOOLS USED IN EDUCATIONAL TECHNOLOGY IN THE EDUCATIONAL PROCESS - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
Our article provides information about the development and implementation of innovative methods in modern education.